Serine‐Assisted Red Luminescence of Copper Nanoclusters for Cr6+ Ion Detection and White‐Light‐Emitting Diodes. Issue 27 (14th July 2022) - Cao, Zheng; Yu, Fanfan; Zhao, Gan; Xiang, Hui; He, Shiyu; Zhang, Mengting; Lin, Jian; Yang, Lina; Liu, Honglin
Abstract: A convenient and facile method was developed for preparing the red luminescent copper nanoclusters (Cu NCs) protected by a combination of 2‐thiobarbituric acid (TBA) and l‐serine (Ser). The synthesized Cu NCs show strong red luminescence with emission wavelength at 680 nm and a quantum yield of 2.5 %. The excellent emission property is attributed to the promoted surface ligand to metal charge transfer and increased surface structure rigidity. The Cu NCs exhibit high stability, abundant surface binding site, good water solubility, along with excitation and temperature dependent luminescent properties, presenting great application potentials. It was found that trace levels of hexavalent chromium (Cr 6+ ) ions can quench the luminescence by inducing NCs aggregation and further growth, making Cu NCs the potential nanoprobe for Cr 6+ ions detection with a limit of detection of 28 nM. Furthermore, the Cu NCs were well applied as the phosphor for fabricating white light emitting diodes (WLEDs) device. Abstract : Red luminescent copper nanoclusters protected by a combination of 2‐thiobarbituric acid and l‐serine with a quantum yield of 2.5 % were prepared. The product exhibits high stability, abundant surface binding site, good water solubility, along with excitation and temperature dependent luminescent properties. It was well applied for sensitive detection of Cr 6+ ions and fabrication of WLEDs.